2005
DOI: 10.1167/iovs.04-1414
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intraocular Pressure on the Transscleral Diffusion of High-Molecular-Weight Compounds

Abstract: Human sclera was permeable to compounds with a molecular weight of up to 150 kDa at transscleral pressures ranging from 0 to 60 mm Hg. Transscleral diffusion was relatively unaffected by the pressure gradient, although for 150-kDa FITC-dextran at 60 mm Hg a 10-fold decrease was observed compared with that at 0 mm Hg. These experiments suggest that high-molecular-weight compounds (e.g., immunoglobulins and oligonucleotides) could be effectively delivered transsclerally to the intraocular tissues under circumsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…This method ensures the intactness of the ocular tissues and maintains the intraocular pressure. We notice that the passive intrascleral diffusivity measured using this set up is similar to the data reported by Maurice and Polgar (1977), but lower than some other reports in literature (Ambati et al, 2000;Cruysberg et al, 2005;Anderson et al, 2008). The difference may be due to the variation in the setup by different groups.…”
Section: Discussionsupporting
confidence: 83%
“…This method ensures the intactness of the ocular tissues and maintains the intraocular pressure. We notice that the passive intrascleral diffusivity measured using this set up is similar to the data reported by Maurice and Polgar (1977), but lower than some other reports in literature (Ambati et al, 2000;Cruysberg et al, 2005;Anderson et al, 2008). The difference may be due to the variation in the setup by different groups.…”
Section: Discussionsupporting
confidence: 83%
“…Scleral permeability has also been investigated after imposing physical effects such as hydration in human [47] and rabbit [30] sclera, cryotherapy [48] , transscleral diode laser [48] , surgical thinning [48] and variations in transscleral pressure [47,49,50] . The diffusion of solutes was found to increase with increase in tissue hydration [30,47] , but removal of glycosaminoglycans did not have a significant effect [30] .…”
Section: Scleramentioning
confidence: 99%
“…It indicated that drug injected into the eyes would be drained out of the eye ball as easy as they go into it through peribulbar injections. Lars (Cruysberg et al 2005) and his colleague reported that higher intraocular pressure (IOP) may reduce the outside-in permeability of sclera. Lower IOP, higher peribulbar pressure, thin sclera and avoiding contact with peribulbar tissue may be an ideal combination for transscleral drug delivery.…”
Section: Discussionmentioning
confidence: 99%